Стихотворение Давида Самойлова «Поэт и гражданин» в свете рецепции «Войны и мира» Льва Толстого - Александрова , Мария Александровна (SlavVaria, 2022)
David Samoilov’s poem “The Poet and the Citizen” in light of the per-ception of Leo Tolstoy’s “War and Peace”. There are in-depth studies of the programmatic poem “The Poet and the Citizen” by David Samoilov from the per-spective of genre tradition and the dialogue with contemporary poets. The reflection on Tolstoy’s legacy as the ideal of the unity of the “children of man-kind” has been a stage in the investigation process in question. However, Samoilov’s stance with respect to Tolstoy’s humanistic precept in the events of the 20th century is still understudied. The present paper analyses the transfor-mation of Tolstoy’s “folk thought” into Samoilov’s intense reflection on the people at war and its embodiment in the imagery of the poem “The Poet and the Citizen”.